Real-world evaluation of safety and efficacy of AHCL systems in young children with type 1 diabetes: a 1-year assessment - Franzone, Daniele; Spacco, Giordano; Piano, Andrea; Siri, Giulia; Tantari, Giacomo; d’Annunzio, Giuseppe; Calevo, Maria Grazia; Maghnie, Mohamad; Minuto, Nicola; Bassi, Marta (Frontiers in Endocrinology, 2025)
Background and aimsManagement of Type 1 Diabetes (T1D) in young children is challenging. A poor glycaemic control during the first years of disease increases the risk of microvascular complications. Moreover, hyperglycaemia and glucose variability have a negative effect on the brain development. Advanced hybrid closed loop (AHCL) systems demonstrated to improve glycaemic control in adolescents and adults with T1D although data on younger children are limited. The aim of the study was to evaluate the safety and the effectiveness of AHCL systems’ off-label use in children aged less than 7 years.MethodsA retrospective single-center study on T1D patients aged less than 7 years using AHCL systems was conducted. Glycated hemoglobin (HbA1c) values, Continuous Glucose Monitoring (CGM) and insulin requirement data were collected at T0 (AHCL starting), T1 (1-month), T2 (3-months) and T3 (1-year).Results41 patients were included in the study. No episode of severe hypoglycaemia occurred. Three patients experienced an episode of ketoacidosis (DKA) due to insulin delivery set occlusion. During the 12-months study period, an improvement in HbA1c value (7.50 vs 6.59%, p<0.001), Time in Range (TIR, +10.21%, p<0.001) and Time in Tight Range (TITR, +7.56%, p=0.003) were observed, with a reduction in time in hyperglycaemia and without an increase in time in hypoglycaemia. The AHCL use increased insulin requirement at 12-months, especially in bolus doses (p<0.001).ConclusionsAlthough AHCL systems are not currently approved for this age group, we have demonstrated their safety and efficacy in children under 7 years with T1D. The use of these systems resulted in significant improvement in glycaemic control without increasing the risk of hypoglycaemia. The impact of early glycaemic control on brain development during the first years of life may support the early introduction of AHCL systems in very young children with T1D. It is essential to gather data that could support the approval of these systems for use in younger age groups.